2015
DOI: 10.1371/journal.pone.0121904
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Neurostimulation in Older Adults Improves Working Memory

Abstract: An increasing concern affecting a growing aging population is working memory (WM) decline. Consequently, there is great interest in improving or stabilizing WM, which drives expanded use of brain training exercises. Such regimens generally result in temporary WM benefits to the trained tasks but minimal transfer of benefit to untrained tasks. Pairing training with neurostimulation may stabilize or improve WM performance by enhancing plasticity and strengthening WM-related cortical networks. We tested this poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
170
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(191 citation statements)
references
References 112 publications
(113 reference statements)
15
170
1
4
Order By: Relevance
“…Some authors have suggested that the DLCPF plays an important role in the planning and proper execution of motor response during WM based tasks (30,31) , in addition, the declarative memory (32) , emotional (33) , and attention (34) are also being used for cognitive rehabilitation with the tDCS. After stimulation of DLPFC area, significant results were found, through analysis of visual and spatial WM outcomes, being in accordance with previous studies on other populations (35)(36)(37) . Other areas such as posterior (38) and lateral parietal (39) are also being used as sities of stimulation, in an attempt to assist in cognitive performance after injury.…”
Section: Discussionsupporting
confidence: 91%
“…Some authors have suggested that the DLCPF plays an important role in the planning and proper execution of motor response during WM based tasks (30,31) , in addition, the declarative memory (32) , emotional (33) , and attention (34) are also being used for cognitive rehabilitation with the tDCS. After stimulation of DLPFC area, significant results were found, through analysis of visual and spatial WM outcomes, being in accordance with previous studies on other populations (35)(36)(37) . Other areas such as posterior (38) and lateral parietal (39) are also being used as sities of stimulation, in an attempt to assist in cognitive performance after injury.…”
Section: Discussionsupporting
confidence: 91%
“…By contrast, some studies suggest that improvements after tDCS interventions may remain weeks or even months after the stimulation. Jeon and Han (2012) ;Park, Seo, Kim, and Ko (2014);and Jones, Stephens, Alam, Bikson, and Berryhill (2015) all found continued improvements to WM performance from a week to 2 months after stimulation. Persistent, long-term changes have also been detected as a function of learning or training in other domains as well, such as motor skill training (Reis et al, 2009), math training (Looi et al, 2016), and episodic memory retrieval (Manenti, Sandrini, Brambilla, & Cotelli, 2016).…”
Section: Baseline Performance and Other Individual Difference Factorsmentioning
confidence: 82%
“…For example, there have been rapid consolidation effects where group differences only begin to emerge in the minutes or hours after stimulation, or become stronger/more robust with time (e.g., Clark et al 2012;Ehsani et al 2016;Hoy et al 2014;Javadi and Cheng 2013;Penolazzi et al 2013;Reis et al 2015). Similarly, overnight consolidation has been enhanced when performance is measured the next day, despite a lack of group differences on day 1 (Koyama et al 2015;Martin et al 2014), and even cognitive training studies that failed to show immediate tDCS-related enhancements have still demonstrated greater tDCS-related retention a couple months later (Jones et al 2015;Martin et al 2013;Stephens and Berryhill 2016).…”
Section: Experimental Evidencementioning
confidence: 99%